2016
DOI: 10.1270/jsbbs.66.260
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of QTLs for traits associated with pre-harvest sprouting resistance in bread wheat (<i>Triticum aestivum</i> L.)

Abstract: Pre-harvest sprouting (PHS) is one of the serious problems for wheat production, especially in rainy regions. Although seed dormancy is the most critical trait for PHS resistance, the control of heading time should also be considered to prevent seed maturation during unfavorable conditions. In addition, awning is known to enhance water absorption by the spike, causing PHS. In this study, we conducted QTL analysis for three PHS resistant related traits, seed dormancy, heading time and awn length, by using recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
(69 reference statements)
1
30
0
Order By: Relevance
“… Hoshino et al (1989) found that a large vernalization requirement delays germination in winter wheat areas where the late wheat is subjected to ear sprouting by monsoon rain. Cao et al (2016) also detected a QTL associated with PHS resistance on the short arm of Chr. 7B where Vrn-B3 is located.…”
Section: Discussionmentioning
confidence: 93%
“… Hoshino et al (1989) found that a large vernalization requirement delays germination in winter wheat areas where the late wheat is subjected to ear sprouting by monsoon rain. Cao et al (2016) also detected a QTL associated with PHS resistance on the short arm of Chr. 7B where Vrn-B3 is located.…”
Section: Discussionmentioning
confidence: 93%
“…These studies have either evaluated PHS resistance directly by testing whole intact spikes in misting chambers or simulated rain events in the field (Somyong et al, 2014; Albrecht et al, 2015), or germination testing of harvest-ripe grain under controlled conditions (Somyong et al, 2014; Zhang et al, 2014; Lin et al, 2015). According to biparental genetic linkage analyses, all 21 chromosomes of wheat reportedly harbor QTL for PHS resistance (Mohan et al, 2009; Cabral et al, 2014; Cao et al, 2016; Fakthongphan et al, 2016), but the most consistently detected regions are located on the group three chromosomes (Kato et al, 2001; Osa et al, 2003; Kulwal et al, 2004; Mori et al, 2005; Liu and Bai, 2010) and Chr 4A (Mares et al, 2005; Chen et al, 2008; Singh et al, 2010; Cabral et al, 2014). The PHS resistance genes underpinning the 3A, 3B, and 3D regions are considered to be tightly linked or pleiotropic with red seed coat color determined by dominant R alleles (Himi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 3AS QTL has been shown to explain up to 58% of the phenotypic variation for PHS (Liu et al, 2008) and has been independently identified in multiple studies as a significant PHS QTL (Liu and Bai, 2010;Nakamura et al, 2011;Graybosch et al, 2013;Cao et al, 2016;Lin et al, 2016;and others). Nakamura et al (2011) established TaPHS1 (formerly termed TaMFT ) as a candidate gene for the 3AS PHS QTL and identified a single nucleotide polymorphism (SNP) mutation in its promoter that upregulated TaPHS1 expression.…”
mentioning
confidence: 97%
“…Previous studies have identified quantitative trait loci (QTLs) significantly affecting PHS on most wheat chromosomes (reviewed by Flintham et al, 2002, andGao et al, 2013). A relatively small number of QTLs account for much of the genetic variability in sprouting variation, with the major QTLs being located on chromosomes 2B, 3A, and 4A (Graybosch et al, 2013, Cao et al, 2016. Some causal genes underlying significant QTLs have been identified and their effects on PHS have been partially characterized, including TaPHS1 (Nakamura et al, 2011, Liu et al, 2013, TaMKK3 (Torada et al, 2016), TaVP1 (Yang et al, 2007), TaSdr , and Tamyb10 (Wang et al, 2016, Lin et al, 2016.…”
mentioning
confidence: 99%